How to Prevent Plagiarism in Student Work - Prusek, Ondřej (Karolinum Press, 2021)
This handbook provide clear yet sufficiently comprehensive guidelines for situations that may arise in connection with plagiarism in the day-to-day academic routine. The handbook offers the opportunity to consider not only the aspects of originality in student work and how to explain the importance of source referencing to students and forms of plagiarism, but also how to recognise plagiarism and what software tools can be used for this purpose. Further, the handbook describes applying penalties for plagiarism and summarises the fundamental antiplagiarism advice from a teacher's perspective into several practical pieces of advice.